Posterior mediastinal Müllerian cyst: a rare cause of pain in a young woman. (July 2017) - Weedle, Rebecca; Conway, Keith; Saftic, Igor; Soo, Alan
Thoracic pain in a young woman carries a wide differential diagnosis. We present the case of a 37-year-old woman who presented with thoracic pain due to a posterior mediastinal Müllerian cyst. Excision was performed by left uniportal video-assisted thoracoscopic surgery. This is the first report to describe thoracic pain that resolved with excision of the cyst.